Avaliação da resposta de genótipos de arroz irrigado a herbicidas do grupo químico das imidazolinonas. - Fonseca, Gabriela de Magalhães da (2011)
The red rice (Oryza sativa) co-exists with the cultivated rice in commercial farmings, becoming one of the main limiting factors for the yield increase in this crop, since this weed competes for the same resources. The rice crop is one of the most important in the world, being the main nutritious source for more than half of the world´s population. Genes for resistance to herbicides have become the best option for the control of this weed. Herbicides that inhibit the ALS enzyme, such as those from the imidazolinone chemical group, are commonly used for weed control in many crops. These ALS inhibitors are currently used for the control of red rice, which is known as Clearfield® technology. This work aimed to study the morphological features that can assist in identifying Only® herbicide tolerance in hydroponic bioassays, and introgression of ALS inhibitor herbicide tolerance genes in cultivars through artificial hybridizations. The rice cultivars used were BRS Sinuelo CL and Puitá INTA CL as imidazolinone herbicide tolerant, and the BRS Pampa, BRS Querência, BRS Atalanta and BRS Fronteira, as sensitive. The variable insertion of the first leaf can be considered an appropriate candidate for study because it discriminates more effectively the responses of different genetic constitutions. Taking in account the doses and periods of development, it can be recommended for use as a morphological marker. The concentration of herbicide that allows better discrimination between tolerant and sensitive genotypes is 25μg L-1 as described in the methodology for this bioassay. The results of this study show that F2 hybrids resulting from crosses between cultivars carrying the allele for herbicide tolerance to the imidazolinone class and conventional rice cultivars, are feasible, enabling the establishment of populations with desirable agronomic characteristics of herbicidetolerant rice, with higher ability to fight the red rice.